The role of Derivatives in the Bankruptcy of Detroit. - Nabar, Uma S. (Tufts Archival Research Center, 2015)
Submitted in partial fulfillment of the degree Masters of International Business at the Fletcher School of Law and Diplomacy. Abstract: The filing for bankruptcy by the city of Detroit on July 18, 2013, represents the largest municipal bankruptcy in the history of the United States. This dubious preeminence was embodied not only in size, but also in complexity. This study seeks to demystify the gargantuan default and how it could have been avoided. Many theories exist about this debacle; from the jet-setting lifestyle of automotive company Management to the “Mafioso” leadership style of its now incarcerated Mayor. Could the underlying source of Detroit’s misfortunes be a result of the bad bets made on interest rates on the advice of financial advisors? The short answer is yes, in part, the interest rate swaps entered into by Detroit on their general-purpose bond issues might have been the straw that broke the camel’s back.